Emotional labour and the practicing psychologist: When the psychologist’s professional emotions go awry - Van Der Merwe, Helen (European Journal for Qualitative Research in Psychotherapy, 2019)
The present study considers practicing psychologists’ accounts when their own emotional reactions within the therapeutic relationship are troubling and unwanted. My understanding of emotions is informed both by Hochschild’s (1979) construct of emotional labour and Wetherell’s (2012) construct of ‘affective practices’. An affective practice perspective maintains that emotions are both constituted actively as people emote and shaped over time as past practice carves out familiar, embodied ways of being. Four focus groups and 11 follow up individual interviews were conducted with early-career psychologists in Aotearoa/New Zealand1. Discourse analysis was used to examine patterns in meaning making. I examine participants’ experiences of unwanted and non-professional emotions and the tension this creates in their self-concept as a contained professional. I consider their stories of how work emotions seeps into their personal lives, and episodes of off-loading about these troubling emotions to colleagues. I look too at their descriptions of how they manage these emotion troubles. I consider why these troubles might be particularly disturbing for a psychologist’s professional identity and self-concept.